Passive Smoking Behaviour and Individual Productivity in Indonesia - Saleh, Edy (Polytechnic of State Finance STAN, 2020)
This research tries to examine the effect of passive smoking behavior at the household level in Indonesia by focusing on the association of smoking behavior of husbands on productivities of their working and non-smoking wives measured by income and number of working hours. Statistically, smoking male prevalence in Indonesia is around 67% while female smoking prevalence is only 2.1%. To do so, this research uses the panel data sourced from Indonesia Family Life Survey (IFLS) 4 and IFLS 5, and compares the results of three statistical methods: OLS, Fixed Effect, and IV method. Overall, the results show that the smoking behavior of husbands is negatively associated with the income of their wives and that there is no correlation with the number of working hours of their wives. This research also finds evidence that the increase of smokers in wives’ community significantly and negatively correlates with their income pointing to community-wide spillover effects.